Who Will Govern the World: New Structure of The International System of Covid-19 Vaccine Producing Countries - Sari, Deasy Silvya; Bainus, Arry; Yulianti, Dina; Aditiany, Savitri; Habibullah, Ali Zahid (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2023)
In early 2020, the international community was faced with Covid-19. At the global level, the COVAX Facility was established to ensure all countries in the world have equal access to Covid-19 vaccines. However, many vaccine-producing countries have undertaken bilateral ways to distribute vaccines directly. The existence of the Covid-19 vaccine is still determined by vaccine manufacturing companies. This article aims to examine the international structure after the outbreak of the Covid-19 pandemic based on the postulate that Covid-19 vaccine-producing countries will become world hegemons in a non-polar world structure. The concepts used are health diplomacy and hegemony. The evolving operational components used to determine world hegemon are vaccine types, consumer countries, and vaccine production capacity. The method used is pseudo-qualitative. The article concludes that (i) world hegemony in terms of vaccine types is China, Russia, the United States, and India; (ii) the world hegemons in terms of the number of consumer countries are the United States, the United Kingdom and China, and (iii) the world hegemons in terms of vaccine production capacity are China, the United States, Germany, and the United Kingdom. Finally, the world hegemons that meet these all criteria are China and the United States.   Pada awal 2020, komunitas internasional dihadapkan dengan Covid-19. Di tingkat global, Fasilitas COVAX didirikan untuk memastikan semua negara di dunia memiliki akses yang sama terhadap vaksin Covid-19. Namun, banyak negara penghasil vaksin telah melakukan cara bilateral untuk mendistribusikan vaksin secara langsung. Keberadaan vaksin Covid-19 masih ditentukan oleh perusahaan pembuat vaksin. Artikel ini bertujuan untuk mengkaji struktur internasional pasca merebaknya pandemi Covid-19 berdasarkan postulat bahwa negara-negara penghasil vaksin Covid-19 akan menjadi hegemoni dunia dalam struktur dunia non-polar. Konsep yang digunakan adalah diplomasi kesehatan dan hegemoni. Komponen operasional yang berkembang yang digunakan untuk menentukan hegemon dunia adalah jenis vaksin, negara konsumen, dan kapasitas produksi vaksin. Metode yang digunakan adalah pseudo-kualitatif. Artikel tersebut menyimpulkan bahwa (i) hegemoni dunia dalam hal jenis vaksin adalah Cina, Rusia, Amerika Serikat, dan India; (ii) hegemoni dunia dalam hal jumlah negara konsumen adalah Amerika Serikat, Inggris dan Cina, dan (iii) hegemoni dunia dalam hal kapasitas produksi vaksin adalah Cina, Amerika Serikat, Jerman, dan Inggris. Akhirnya, hegemoni dunia yang memenuhi semua kriteria ini adalah Cina dan Amerika Serikat.